Capital Buffer Dynamics and Risk-Taking Behaviour of Nigerian Commercial Banks in the Post-Reform Era - Ngozi Okonjo-Iweala; Charles Chukwuma Soludo; Folarin Ikpesu; Tolulope Osinubi; Kazeem O. Ajide (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2024)
This study examines the long-run determinants of capital buffer accumulation and risk-taking behaviour among listed Nigerian commercial banks during the period H1:2012 to H2:2023 an era marked by successive Basel III-aligned regulatory reforms, oil price shocks, pronounced naira depreciation, and persistent macroeconomic volatility. The purpose of this study is to investigate how bank-specific variables, macroeconomic cycle indicators, oil revenue cycles, and regulatory pressure jointly shape the long-run capital and risk-taking decisions of Nigerian banks a question that existing short-run simultaneous equation frameworks have been unable to adequately address. The methodology employs a Panel Autoregressive Distributed Lag (Panel ARDL) model estimated using the Pooled Mean Group (PMG) technique on hand-collected semi-annual data from eleven listed Nigerian commercial banks, incorporating a novel oil revenue cycle variable (OIL) to capture the compound procyclicality unique to Nigeria's resource-dependent macroeconomic structure. The findings reveal that Nigerian banks exhibit moral hazard behaviour, whereby rising non-performing loans erode capital buffers in the long run through the risk-weight channel rather than triggering proactive capital rebuilding. Capital buffer adjustment operates primarily through lending contraction and leverage compression rather than equity issuance a structural constraint imposed by the shallowness of Nigeria's domestic equity market. While higher capital buffers significantly reduce long-run risk-taking, regulatory pressure simultaneously induces undercapitalised banks to increase risk exposure, confirming a moral hazard channel. Both the non-oil business cycle and the oil revenue cycle generate compound procyclicality in Nigerian bank capital and risk-taking behaviour. The originality of this study lies in its introduction of the oil revenue cycle as an explicit explanatory variable and its application of the Panel ARDL-PMG framework — which disentangles long-run equilibrium effects from short-run dynamics to the Nigerian banking context for the first time. The findings carry direct implications for the CBN's 2024 recapitalization mandate and macro-prudential policy design in resource-dependent banking systems.